نظرية العقاب التشريعي بين التشكبل التاريخي والوعي المقصدي: (Theory of Punishment in Islamic Law between Historical Formation and Intentional Understanding) - إبراهيم محمد زين (At-Tajdid - Intellectual Refereed Journal, 2022)
-